Correction: Richards et al. Indian Ornamental Tarantula (Poecilotheria regalis) Venom Affects Myoblast Function and Causes Skeletal Muscle Damage. Cells 2023, 12, 2074 - Nicholas J. Richards; Ali Alqallaf; Robert D. Mitchell; Andrew Parnell; Husain Bin Haidar; José R. Almeida; Jarred Williams; Pradeep Vijayakumar; Adedoyin Balogun; Antonios Matsakas; Steven A. Trim; Ketan Patel; et al. (Cells)
In the original publication [...]